Tetragonal heusler compounds for spintronics - Felser, Claudia; Alijani, Vajiheh; Winterlik, Juergen; Chadov, Stanislav; Nayak, Ajaya K. (IEEE Transactions on Magnetics, 2013)
With respect to the requirements of spin torque transfer (STT) materials, one the most promising materials families are the tunable tetragonal Heusler compounds based on rm Mn2YZ (Y=rm Co,rm Fe,rm Ni,rm Rh,…; Z=rm Al, Ga, Sn). They form the inverse cubic Heusler structure with three distinct magnetic sublattices, which allows a fine tuning of the magnetic properties. Starting with the stoichiometric rm Mn3rm Ga compound, we explored the complete phase diagram of rm Mn3-rm xY-rm xZ (Y=rm Co, Fe, Ni and Z=rm Ga ). All series exhibit thermally stable magnetic properties. As we demonstrate, rm Mn3-rm xrm Fe-rm xrm Ga series, which are tetragonal over the whole range of compositions, are good as hard magnets, whereas magnetically more weak rm Mn3-rm xrm Ni-rm xrm Ga series exhibit the shape memory phenomenon. Even more surprising properties are found in the Co-based series. On the one hand, the Co-poor (rm x<0.5) rm Mn3-rm xrm Co-rm xrm Ga tetragonal alloys are well-suited for the STT. At the same time, the Co-rich cubic series (0.5<rm x<1) are half-metallic ferromagnets, following the Slater-Pauling rule, similar to rm Co2YZ cubic Heusler compounds. © 1965-2012 IEEE.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Heusler compounds; magnetic properties; materials science; spin torque transfer; spintronics